Microencapsulation of Lactobacillus bulgaricus and survival assays under simulated gastrointestinal conditions. (February 2017) - Chen, Hai-Yan; Li, Xiang-Yi; Liu, Bing-Jie; Meng, Xiang-Hong
Highlights: Lactobacillus bulgaricus was embedded in WPI microcapsules with alginate coating. Microencapsulation protected probiotics under simulated gastrointestinal conditions. Lyoprotectants improved the survival of encapsulated bacteria during freeze-drying. Low temperature and microencapsulation improved survival of bacteria during storage. Abstract: Probiotic Lactobacillus bulgaricus was microencapsulated in whey protein isolate using emulsion technique with transglutaminase-induced gelation and alginate coating. The high encapsulation efficiency (95.28 ± 2.31%) achieved in experiments demonstrated the compatibility between wall materials and the probiotic strain. In both simulated gastric juice and bile tolerance tests, microencapsulation provided significant protection against cell mortality compared to the control. Results from optical and scan electron microscopy observations showed complete encapsulation of probiotic cells in the wall materials, suggesting that the protection was provided by the strong penetration-resistant physical barriers of the microcapsules. During the freeze-drying process, the wall materials alone provided little protection against cell mortality. But with additional lyoprotectants, the survival rates of probiotic cells were improved remarkably. In addition, microencapsulated cells exhibited much better retainability of cell survival during storage, especially under low temperatures.